PENGUATAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SENI BUDAYA DAN PRAKARYA PADA PESERTA DIDIK KELAS IV SD JAMBE AGUNG BATUBULAN (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Art and culture significantly benefit human life personally and socially, so it stands to reason that art and culture are included in the primary education curriculum. The lack of strengthening character education in subjects at Jambe Agung Elementary School, Batubulan can be fostered through learning Arts, Culture, and Crafts (ACaC). Character strengthening can be formed through ACaC learning, where ACaC learning aims to train psychomotor skills, creativity and at,t attitudes that contain character education values. This research analyzes the approach to strengthening character education and the constraints and efforts made in strengthening character education through ACaC learning for grade IV students at Jambe Agung Elementary School. This descriptive quality research data uses observation techniques, interviews, literature studies, and document studies. The results showed that (1) The approach to strengthening character education in ACaC learning for grade IV students includes teacher example, empowerment and culture, integrating character values in RPP, and methods of strengthening character education used during learning. (2) The obstacles faced in implementing strengthening character education through AcaC learning for grade IV students are obstacles in integrating ACaC content with thematic and limited SBdP learning time. Then the efforts made by teachers to overcome these obstacles are by finding supporting teaching materials from the internet and linking learning with real examples and teachers trying to adjust ACaC learning activities based on the available time.